THE EFFECT OF ROA, NPM, EVA, AND MVA ON STOCK RETURN ON MANUFACTURING COMPANIES IN THE AUTOMOTIVE SUBSECTOR 2010-2019 - Destria Kurnianti; Suherman; Arnianggi Kurnia Wardani (Econosains Jurnal Online Ekonomi dan Pendidikan, 2021)
This study aims to determine the effect of ROA, NPM, EVA, and MVA on stock returns in automotive manufacturing companies for the 2010-2019 period. The sample of this research is 7 manufacturing companies in the automotive sub-sector for the 2010-2019 period in Indonesia (38 observations). This research uses unbalanced panel data with a Fixed Effect Model approach. The theory used in this research is signal theory. Testing the data using panel data regression test, classical assumption test, coefficient of determination test, and hypothesis t-test. The test results show that Return On Assets (ROA) has a significant positive effect partially on stock returns, while Net Profit Margin (NPM), Economic Value Added (EVA), and Market Value Added (MVA) partially have a negative effect on stock returns.